F. A. BERNALDO DE QUIRÓS Y BENAVIDES, «Romance d’"El Caballu" & Poesía en castellanu», ed. de Xuan C. Busto Cortina, Uviéu, Universidá d’Uviéu, 2019, 460 págs. - Olay Valdés, Rodrigo (Cuadernos de Estudios del Siglo XVIII, 2019)
SIN RESUMEN